Trans to cis photo-isomerization in merocyanine dysprosium and yttrium complexes. Issue 12 (22nd February 2018) - Selvanathan, Pramila; Dorcet, Vincent; Roisnel, Thierry; Bernot, Kévin; Huang, Gang; Le Guennic, Boris; Norel, Lucie; Rigaut, Stéphane
Abstract : A unique light-switching behavior is revealed in Yttrium(iii ) and Dysprosium(iii ) merocyanine complexes through NMR and AC magnetometry experiments. Its impact on slow relaxation of magnetization is described. Abstract : We report the synthesis of two lanthanide complexes including a chelating merocyanine (MC) ligand obtained from the reaction of a bis(pyridinemethyl)amine substituted spiropyran with yttrium(iii ) or dysprosium(iii ) triflate salts, whose structures were confirmed both in the solid state and in solution by single crystal X-ray diffraction studies and NMR investigations. The obtained merocyanine metal complexes can reversibly undergo a photo-triggered transformation consisting of a partial isomerization of the trans -merocyanine ligand to its cis isomer ( cis -MC) providing complexes in which the metal–phenolate bond is retained. SQUID magnetometry experiments in combination with ab initio calculations were used to evidence and rationalize the single-molecule magnet behavior of the dysprosium complex and to probe the changes in the dysprosium ion local environment upon photo-isomerization.